Análise dos impactos dos cenários de mudanças climáticas na produção vegetal na região do planalto norte do Rio Grande do Sul, com uso do modelo EPIC - Ihlenfeld, Ricardo Germano Kürten (2016)
This study estimates the climatic effects for three scenarios of climate change in six cultures in continuous rotation, using the EPIC model (William et al.) version 0810, It was 19 years of observed monitoring data (1994-2014) in the long-term experimental plot of EMBRAPA / CNPT in Passo Fundo, RS, in a Oxisol dystrophic clayey humic (LVd). The EPIC model was calibrated according WANG, et al. (2012), with performance estimated by the R2 of 0.87, PBIAS (bias) of 1% and NSE 0.73. The three proposed scenarios based in the literature for the Southern Region of Brazil, altering (a) the maximum and minimum monthly temperatures (b) the monthly rainfall and rainfall standard deviations, with periods of +15 and -15 years from the central dates, were C1 (2040): + 1°C + 10% (mm); C2 (2070): + 2°C to + 20% (mm); and C3 (2100): +3°C and + 30% (mm). The results were compared at each period and scenario, with the corresponding results of the simulations of the scenarios, with the current climatic pattern (current variability) named CO, whose varibles were obtained from a climate data series from 1984 to 2014 (30 years). The results conclude that keeping the same growing conditions and rotation, there will be a progressive reduction in grain yield in soybean, corn, grain sorghum, oat and barley and dry matter in the crop of hairy vetch. The main causes of this reduction in result are attributed to photorespiration reactions in species of the C3 group, the increased demand and losses of nitrogen, rain deficit (despite the increase in rainfall), and an increased water loss through evapotranspiration (water stress), increase of dry periods (intervals between rainy weather) and soil management characteristics as expected. The most important finding was the actual viability of the use of mathematical models for Brazilian conditions, as a robust tool, necessary to modernize the management of research projects, teaching activities, management of agricultural production, as well as monitoring and environmental assessment.